Participatory Forum Theatre for AIDS Education - Durden, Emma; Nduhura, Dominique (Culture, Communication and Media Studies, 2003)
This paper examines the use of the participatory forum theatre methodology for HIV/AIDS education in a factory setting in Durban, 2003. The paper explores the field of Entertainment Education (EE), which is the strategic use of entertainment forms for educational purposes, and how EE is used in development communication. We investigate participatory communication theory, the work of Brazilian educationalist Paulo Freire, and the principles that inform Augusto Boal’s forum theatre methodology practice. EE strategies and communication and behavioural change theories inform the design and practice of the PST (problem solving theatre) project, which is the case study for this research project. This paper outlines the process of the PST project, investigating the environment at the chosen factory site, and the prevailing knowledge and attitudes towards HIV/AIDS, the creation of an appropriate forum theatre play, as well as observations and comments on the performance at the factory. Final summative research investigates the impact that the forum theatre had on the audience, and our conclusion suggests how forum theatre, as an EE strategy, can be further used in a factory setting
Keywords: strategies; behavioural change; communication